2017
DOI: 10.1016/j.vaccine.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

The role of anti-NHba antibody in bactericidal activity elicited by the meningococcal serogroup B vaccine, MenB-4C

Abstract: Background MenB-4C (Bexsero®) is a multicomponent serogroup B meningococcal vaccine. For vaccine licensure, efficacy was inferred from serum bactericidal antibody (SBA) against three antigen-specific indicator strains. The bactericidal role of antibody to the fourth vaccine antigen, Neisserial Heparin binding antigen (NHba), is incompletely understood. Methods We identified nine adults immunized with two or three doses of MenB-4C who had sufficient volumes of sera and >3-fold increases in SBA titer against a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
4
9
0
Order By: Relevance
“…Mouse anti-NHba antiserum had a titer of < 10. The relative resistance to anti-NHba was similar to previous findings that some NHba-expressing serogroup B meningococcal strains resist MenB-4C vaccine–elicited anti-NHba serum bactericidal activity (SBA) in humans ( 7 ).…”
Section: Case Reportsupporting
confidence: 87%
“…Mouse anti-NHba antiserum had a titer of < 10. The relative resistance to anti-NHba was similar to previous findings that some NHba-expressing serogroup B meningococcal strains resist MenB-4C vaccine–elicited anti-NHba serum bactericidal activity (SBA) in humans ( 7 ).…”
Section: Case Reportsupporting
confidence: 87%
“…In addition to NHBA sequence and expression level, a combination of other factors is also likely to contribute to the SBA and OPA titres seen for different strains, including intrinsic strain features that can affect complement regulation and susceptibility of each strain to human serum used as a complement source. Similar intrinsic differences between strains have also been reported for anti-NHBA [34] and anti-fHbp bactericidal activity against N. meningitidis [35,36]. The SBA titres ranged from 50 to 1600 for the different vaccine antigens and formulations against different strains.…”
Section: Discussionsupporting
confidence: 75%
“…8,11,39 Previous studies demonstrated polyclonal sera targeting different meningococcal antigens can synergistically activate complement. 21,22 To investigate the molecular mechanisms involved in such synergy, we selected two well-known and characterized meningococcal antigens, fHbp and NHBA, as a model. The reason for this choice relies on the wide body of knowledge about the immunological properties of these two antigens.…”
Section: Discussionmentioning
confidence: 99%